PERANCANGAN SISTEM PENGISIAN BATTERY CHARGER DENGAN PEMBANGKIT LISTRIK TENAGA ANGIN - Supardi, Wayan; Putra Adnyana, G.A; Suarbawa, K. N; Wibawa, K. P. (BULETIN FISIKA; Vol 15 No 1 (2014): BULETIN FISIKA, 2014)
A system of fillng charger using wind-powered electricity has been made. A battery charger system using a four cornered windmill powered by a generator as the mean to change the movement energy from the windmill in to electricity. The current produced by the generator before it enters the battery is connected to the clain of chargers which fills the battery charger. Battery charger keeps electrical energy the battery charger will be filled when the current output from the generator is greater than 6,00 volt, if it is less than 6,00 volt it will not be filled. The length of time to fill cannot be determined because if depends on the speed of the relation of the generator.